2022
DOI: 10.3389/fendo.2022.992540
|View full text |Cite
|
Sign up to set email alerts
|

Mouse models and human islet transplantation sites for intravital imaging

Abstract: Human islet transplantations into rodent models are an essential tool to aid in the development and testing of islet and cellular-based therapies for diabetes prevention and treatment. Through the ability to evaluate human islets in an in vivo setting, these studies allow for experimental approaches to answer questions surrounding normal and disease pathophysiology that cannot be answered using other in vitro and in vivo techniques alone. Intravital microscopy enables imaging of tissues in living organisms wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 104 publications
0
9
0
Order By: Relevance
“…Most studies have primarily concentrated on non-fully mature DCs, evaluating the effects of compounds like 1α,25- Dihydroxyvitamin D3 on DCs maturation and activation, but none have investigated their potential to transform fully mature DCs isolated from individuals with T1DM into a tolerogenic phenotype 70,71 . Similarly, most human islet transplantation survival and functional studies have been carried out in immunodeficient mice in order to prevent rejection 72 . Consequently, our findings hold significant implications for human studies, as reversing the disease will require resolution of the chronic pro-inflammatory/autoimmune attack predominantly steered by islet self-antigen activated macrophages and dendritic cells, which play a central role in the induction of T-cell expansion and subsequent β-cell destruction 73 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies have primarily concentrated on non-fully mature DCs, evaluating the effects of compounds like 1α,25- Dihydroxyvitamin D3 on DCs maturation and activation, but none have investigated their potential to transform fully mature DCs isolated from individuals with T1DM into a tolerogenic phenotype 70,71 . Similarly, most human islet transplantation survival and functional studies have been carried out in immunodeficient mice in order to prevent rejection 72 . Consequently, our findings hold significant implications for human studies, as reversing the disease will require resolution of the chronic pro-inflammatory/autoimmune attack predominantly steered by islet self-antigen activated macrophages and dendritic cells, which play a central role in the induction of T-cell expansion and subsequent β-cell destruction 73 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, most human islet transplantation survival and functional studies have been carried out in immunodeficient mice to prevent rejection (69). Herein, we selected the STZ-treated C57/BL6J mouse model with the specific intention of expanding on our previous findings on BL001 tolerizing a pro-inflammatory environment, key for the sustained engraftment and long-term functionality of human islets (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glycemic control and islet cell damage in SARS-CoV-2-infected islet organoids could then be assessed both in vitro and in vivo, which would help us to further understand the mechanism of infection and define a road map for new therapeutics ( Figure 1 ). The intravital imaging and microscopic techniques of islet organoids also allow the exploration of dynamic changes after transplantation into mouse models [ 99 ].…”
Section: Strengths and Challenges Of Using Islet Organoid Modelsmentioning
confidence: 99%
“…The angiogenic capacity of pancreatic islets has been explored using animal models (Speier et al, 2008; Wagner et al, 2022), which have revealed specific angiogenic secretions from the islets, such as vascular growth factor A (VEGF‐A) (Brissova et al, 2006; Xiong et al, 2020), the significant contribution of the donor's endothelium to the formation of a vascular network after transplantation (Brissova et al, 2004; Linn et al, 2003; Nyqvist et al, 2005), and the effects of immunosuppressive drugs on vascular formation (Nishimura et al, 2013). However, analyzing individual islets for their molecular functions in animal models is technically difficult, making it challenging to unveil the detailed mechanisms of vascular formation induced by islets.…”
Section: Introductionmentioning
confidence: 99%